Policy Recommendations to Enhance the Competitive Capacity of Thai Health and Beauty Enterprises in the ASEAN Arena - Chancharoen, Suramon (Ph.D. in Social Sciences Journal, 2026)
The research article aims to study (1) examine the levels of government policies, government support, organizational innovation, brand equity, and competitive organization of Thai entrepreneurs, (2) study the influence of government policies, government support, organizational innovation and brand equity on competitive organization of Thai entrepreneurs and (3) develop policy recommendations to enhance the competitiveness of Thai health and beauty businesses in the ASEAN market. A mixed-methods research design was employed. The quantitative phase collected data through questionnaires from 440 executives of health and beauty businesses registered with the Department of Health Service Support in Thailand. Statistical analyses included mean, standard deviation, and structural equation modeling. The qualitative research involved in-depth interviews with 15 experts, and the data was analyzed using content analysis techniques. Findings are as follows: (1) The competitiveness of Thai entrepreneurs, organizational innovation, government policies, government support, and brand equity, all at a high level. (M = 4.38, 4.36, 4.33, 4.14, 3.95) (2) Government support organizational innovation, government policies, and brand equity, had influence on competitiveness, with a coefficient of influence of .97, .86, .67, and .41, respectively. (3) The policy recommendations to enhance the competitiveness of Thai health and beauty businesses in the ASEAN arena include the following: promote organizational innovation, improve and develop government policies that facilitate the expansion of businesses abroad, create a supportive government system to strengthen businesses, develop and enhance brand equity and develop networks and cooperation between businesses in ASEAN.